Incredible India 2.0 : synergies for growth and governance (New Delhi Rupa, 2019)
In incredible India 2.0, Amitabh Kant covers a wide range of aspects that India must achieve to become a world-leading nation. From developing clusters that foster productivity and innovation, thereby making India. The global hub for seamlessly doing business, to creating an ecosystem of shared mobility to become a critical enabler of growth in urban areas, to the manner in which the aspirational district programme is forging the first step to ensuring a nationally inclusive development strategy, these developments show the extent of the path-breaking solutions for key sectors that can emerge as the cornerstone for India$1 (Bs future growths
Keywords: Technological innovations; Economic development; Internet in public administration